2013
DOI: 10.1001/jamaoto.2013.1111
|View full text |Cite
|
Sign up to set email alerts
|

Operative Management of Choanal Atresia

Abstract: Our revision rate after initial endoscopic repair of choanal atresia was low and was unaffected by adjuvant mitomycin C therapy or stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 18 publications
5
45
0
5
Order By: Relevance
“…22 Tessier et al 10 reported the mean operation age of 80 patients with bilateral and unilateral CCA was between 3 days and 17 years, and in another study (31 patients), it was between 3 days and 15 years. 16 The mean follow-up time reported in studies is between 6 and 46 months. 6,10,14,18,23Y25 In our study, the mean age was 37 days in group I and 12.3 years in group II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Tessier et al 10 reported the mean operation age of 80 patients with bilateral and unilateral CCA was between 3 days and 17 years, and in another study (31 patients), it was between 3 days and 15 years. 16 The mean follow-up time reported in studies is between 6 and 46 months. 6,10,14,18,23Y25 In our study, the mean age was 37 days in group I and 12.3 years in group II.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similar results were also reported in many studies. 8,10,11,14,16,17,21,23 The patients with stenting should receive antibiotic treatment to reduce the incidence of infection. 10,16,17 We use stent in all our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Newman et al, 6 deals with 33 patients (31 endoscopic, 2 transnasal). Forty-three sides were operates endoscopically, 9 required revision surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies comparing results with and without the use of stents indicate higher rates of restenosis with stenting [34,51,60,62,[68][69][70][71][72][73]. Stents were reported to induce complications: major granulation tissue formation, intranasal inflammation and infection, excoriation or erosion of the nares, columellar necrosis, septal injuries or perforation, premature extrusion, dislodgement, stent blockage, discomfort and pain [ (53,58,70,72,74,75].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, referral is often delayed due to the lack of up-to-date information on therapeutic modalities available nowadays for management of CCA. The old recommendation advocated in unilateral CCA was to postpone surgery for many years [1,71] hence leaving the child with symptoms of nasal obstruction and exposed to chronic nose and paranasal sinus infection as well as to chronic serous otitis media. This explains why, in the present study, the youngest child operated for unilateral CCA was 6 days old and the oldest 13 years old.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%